2D Rare Earth Material (EuOCl) with Ultra‐Narrow Photoluminescence at Room Temperature. Issue 20 (2nd April 2021) - Chen, Ping; Li, Zexin; Li, Dongyan; Pi, Lejing; Liu, Xitao; Luo, Junhua; Zhou, Xing; Zhai, Tianyou
Abstract: High color purity and color rendition of 2D luminescent materials have long been pursued for applications in low‐dimensional lighting, display, biolabeling, and laser. However, the reported photoluminescence (PL) linewidth of most 2D luminescent materials is about dozens of meV. Herein, a brand‐new luminescent system of 2D rare earth (RE) material EuOCl (1.1 nm) with ultra‐narrow linewidth (1.2 meV) at room temperature is successfully synthesized via chemical vapor deposition (CVD). The linewidth of EuOCl flakes at room temperature is even narrower than most 2D luminescent materials and heterostructures detected at below 10 K. Impressively, the as‐synthesized EuOCl flakes show abnormal temperature‐dependent photoluminescent properties, which is absolutely different from the relatively stable 4f–4f transitions in RE owing to shielding from outer shell electrons. J‐mixing effect has been successfully applied for this phenomenon. Undoubtedly, luminescent 2D EuOCl flakes will open new territory for the applications of 2D RE materials in the 2D luminescent areas, especially for the applications at room temperature. Abstract : This work presents the synthesis of 2D ultrathin RE materials EuOCl (1.1 nm) via salt‐assisted chemical vapor deposition (CVD) methods. Impressively, the as‐synthesized EuOCl flakes have excellent photoluminescence properties with ultra‐narrow linewidth down to 1.2 meV at room temperature, which is much narrower than most 2D luminescent materials as well as van der Waals heterostructures.